A youthful urban commons: High schoolers reimagine the schoolyard as public space by using the placemaking approach - Bradley, Anna Louise; Reich, Clara J.; Curtis, Adam (Sens public)

(untitled) (Département des littératures de langue française, 2024)
While public space is meant for all to participate in and use, it does not inherently mean it is accessible, suitable, or appropriate for all users. Likewise, the urban commons, a concept that posits the collective pool and ownership of resources in an urban community, does not automatically qualify all residents to have access and democratic participation for such resources. The objective of this exploration is to exemplify, understand, and synthesise the best practices contributing to the production of generative urban commons. Placemaking will be explored critically in this paper first to understand the concept at its root, the pitfalls if not followed conscientiously, and the methodological underpinnings of the approach. To illustrate practical applications to these assertions, this paper exemplifies PlaceCity: Placemaking for Sustainable, Thriving Cities, distinctly, the case study of Hersleb High School in Gronland, Oslo. The Hersleb High Schoolers are at the forefront of this case study, as the PlaceCity project sought to engage and co-create the area together with the youth to foster a collective sense of belonging, hope for the future, and enliven the public spaces.